THE DEVELOPMENT OF INQUIRIES LEARNING MODEL WITH A CONTEXTUAL APPROACH - Muh Bukhari (Scientium Educational Review, 2022)
This study aims to produce an inquiry learning model with a contextual approach to social studies learning, which is realized into three product forms: teacher books, student books, and model books. Field trials in this study consisted of 20 students, eight male students and twelve female students. This research uses a developmental research model. This development research uses the Borg and Gall development model, which is carried out in five stages: the needs analysis stage, the design stage, the prototyping stage, the field trial stage, and the product revision stage. The results of this study indicate that: (1) Based on the validator's assessment, the products developed in the form of teacher books, student books, and model books are included in the "good enough" category. The results of field trials showed that students' average value reached 74.5. the percentage of student learning completeness reaches 85%. (3) Student learning activities are included in the "active" category with an average score of 47. It is concluded that the product development of the Inquiry learning model with a contextual approach to social studies learning in the classroom is appropriate for use in learning in elementary schools.